Support for private research and development in OECD countries on the rise but increasingly inefficient - Heike Belitz (DIW Economic Bulletin, 2016)
The majority of OECD member states promote companies' research and development (R&D) activities by providing project funding. Recently, in many countries, tax incentives have also begun to play an increasingly important role. The present study examines the level of R&D support in 18 OECD countries and explores how efficient the system of funding actually is. The main findings show that in the majority of the countries studied, the share of research and development expenditures funded by the government is on the increase. The system has become less efficient, however. Increasingly frequently, one euro of public funding fails to result in a corresponding increase in private R&D spending. In countries with high funding rates and substantial tax incentives (such as France and the UK), companies' spending relative to economic output has not increased any faster than in countries with considerably lower funding rates and no tax incentives at all (such as Germany).
Keywords: O31; O38; O57; 330; business R&D; government support; tax incentives